Tinjauan Yuridis Terhadap Disparitas Pidana Dalam Perkara Tindak Pidana Pencurian - Pitaloka, Magdalena Shintya (2016)
This study aims to explain the factors causing the disparity in criminal and legal consequences of criminal disparities in the criminal case of theft. The method used is the doctrinal normative legal research methods. This type of research is descriptive research, which is to give an idea as thoroughly as possible about the review jurisdiction over criminal disparities in the criminal case of theft. The results showed that the factors that led to the disparity of criminal that is derived from the legal system (Law system Continental Europe), disparity in criminal sourced from the judge, in which the basic imposition of the decision must consider the purpose of sentencing, disparity criminal sourced from the defendant, in where the criminal punishment can not be separated from the defendant state that aggravating circumstance and ease. The legal consequences arising from the disparity criminal defendant was treated unfairly by a judge who feared will lead to public antipathy to the law and our judicial institutions, so as to give rise to vigilantism without going through a judicial process.